The Research Progress of Trastuzumab-Induced Cardiotoxicity in HER-2-Positive Breast Cancer Treatment - Lin, Mengmeng; Xiong, Weiping; Wang, Shiyuan; Li, Yingying; Hou, Chunying; Li, Chunyu; Li, Guohui (Frontiers in Cardiovascular Medicine, 2022)
In recent years, the incidence of breast cancer has been increasing on an annual basis. Human epidermal growth factor receptor-2 (HER-2) is overexpressed in 15-20% human breast cancers, which is associated with poor prognosis and a high recurrence rate. Trastuzumab is the first humanized monoclonal antibody against HER-2. The most significant adverse effect of trastuzumab is cardiotoxicity, which has become an important factor in limiting the safe use of the drug. Unfortunately, the mechanism causing this cardiotoxicity is still not completely understood, and the use of preventive interventions remains controversial. This article focuses on trastuzumab-induced cardiotoxicity, reviewing the clinical application, potential cardiotoxicity, mechanism and discussing the potential interventions through summarizing related researches over the past tens of years.